The Effectiveness of Blended Learning in English Speaking Skill for Undergraduate in 4.0 - Sari, Desvita; Sofyan, Rudy; Nasution, Ely Hayati (RADIANT: Journal of Applied, Social, and Education Studies, 2021)
This research deals with the students’ achievement of speaking skills and perception towards Implementing Individual Rotation of blended learning. The writers discuss the effectiveness of blended learning implemented in the pre-test and post-test of English speaking skill achievement of the 2nd semester of English Department students of the University of Sumatera Utara and their perception of it. This research aims to find out how the Individual Rotation Model of blended learning improves students’ English speaking skill achievement using the Learn Social platform and to find out students’ perceptions after implementing blended learning. In conducting this research, the writers apply descriptive with a mixed-method (Creswell & Plano Clark, 2011) analyzing the students’ achievement found in the pre-test and post-test and giving the online questionnaire to assess their perception towards blended learning. The data shows that the student's achievement in the post-test (Mean=87%) was higher than the pre-test (Mean=85%) out of 50 students. According to the data, 90% of the 42 students gave a positive response to blended learning. The result showed Individual Rotation Model improves the English speaking skill achievement especially in the components of speaking skill namely, vocabulary, grammar, and comprehension, and effective to be implemented for undergraduate students in the era of industrial revolution 4.0.